Religion-Based Decision Making in Indian Multinationals: A Multi-faith Study of Ethical Virtues and Mindsets - Chan, C.; Ananthram, Subra (Springer Netherlands, 2017)
The convergence of India’s rich cultural and religious heritage with its rapidly transforming economy provides a unique opportunity to understand how senior executives navigate the demands of the business environment within the context of their religious convictions. Forty senior executives with varying religious backgrounds and global responsibilities within Indian multinational corporations participated in this study. Drawing from virtue ethics theory and using systematic content analysis, several themes emerged for ethical virtues (empathy, sympathy, humanity, justice, fairness, temperance, integrity, transparency, governance, conscientiousness, transcendence, wisdom, moral fortitude and determination). The analysis illustrates how these deeply seated ethical virtues helped to form and refine these executives’ ethical mindsets via guiding principles such as an ethical culture, environment, molding, education, commitment and leadership. In turn, these ethical mindsets influenced the executives’ ethical decision-making processes. We find that these executives’ ethical virtues and mindsets are inspired by their religious backgrounds. In summary, a very complex mental tug-of-war appears to take place as these executives rationalize and negotiate unethical circumstances while being cognizant of personal religious beliefs. We contend that in a pluralistic multi-faith society such as India, it is critical for corporations to align the virtues of its senior executives with those of the corporation so that virtues are applied consistently when dealing with various stakeholders. The findings present several theoretical and practical implications, which are discussed.